Sakralność życia w ciele w nauczaniu Jana Pawła II - Lubowicki, Kazimierz (Verbum Vitae, 2022)
Based on the Wednesday catecheses of John Paul II on the theology of the body, the article presents the essential elements of the ethos of human corporeality. It highlights the innovative approach of the Pope, who changed the perspective of teaching in this realm. When speaking of married life, for example, it does not start with duties and principles, nor does it stop at them, but instead shows those obligations and principles as an expression of a sublime call to holiness. In its own way, this approach “flows into the deep”, teaching not so much “freedom from” as “freedom to”. For the sake of cognitive realism, the Pope made Scripture the starting point for this teaching, where, especially in the Book of Genesis, he finds “God’s plan for marriage and family”. In characterizing the ethos of the body, attention is drawn to the beauty of the body, closely related to human dignity, even if it is crushed by disease and weakness. To this essential beauty, the mature response of faith is emotion and delight. As to the gift of sexuality, it is characterized by unity in diversity, by absolute equality, and by mutual complementarity. Purity is presented in an original way, as a natural consequence of one’s sense of the sacredness (sacrum) of the human body. Manichean contempt for the body is dismissed as a heresy alien to Christianity: The human body cannot be held suspect, but only summoned. An eloquent sign of the body’s call to holiness is the fact that sexual intercourse is an integral part of the sacramental sign of marriage (ratum et consumatum).